Identification of a Novel Immune-Related lncRNA CTD-2288O8.1 Regulating Cisplatin Resistance in Ovarian Cancer Based on Integrated Analysis - Liu, Tingwei; Shen, Jiacheng; He, Qizhi; Xu, Shaohua (Frontiers in Genetics, 2022)
Ovarian cancer (OC) is an immunologically active malignancy, which chemo-resistance is a crucial factor leading to the poor prognosis. However, further exploration of the potential mechanism between immune characteristics and cisplatin-resistance in OC is still reasonably necessary. Our study focused on the role of cisplatin-resistance-related lncRNAs on mediating OC tumor immune microenvironment (TIME) through an integrative analysis based on The Cancer Genome Atlas (TCGA) database. Firstly, the cisplatin-resistance-related differentially expressed lncRNAs (DELs) and mRNAs (DEMs) were obtained to construct a DELs-DEMs co-expression network. Protein-protein interaction (PPI) network and pivot analysis were preliminarily performed to reveal the relevance of these lncRNAs with tumor immune response. Secondly, the lncRNA CTD-2288O8.1 was identified as a key gene for cisplatin-resistance in OC by qRT-PCR and survival analysis. Then gain-and-loss-of-function assays (Cell Counting Kit-8 (CCK-8) assay, wound-healing scratch assay, transwell assay, and colony formation assay) were further proved the role of CTD-2288O8.1 in OC progression. Thirdly, Gene Set Enrichment Analysis (GSEA) was applied along with the correlation analyses of CTD-2288O8.1 with ImmuneScore, tumor-infiltrating immune cells (TICs), and immune inhibitory checkpoint molecules, illustrating that CTD-2288O8.1 was strongly associated with TIME and has the potential to predict the effect of OC immunotherapy. Besides, basic experiments demonstrated that the expression of CTD-2288O8.1 significantly impacted the EGFR/AKT signal pathway activity of tumor cells and M2 polarization of macrophages. Taking together, our study revealed cisplatin-resistance-related lncRNAs closely linked with tumor immunity in OC, underscoring the potential mechanism of the immune environment in conferring resistance. CTD-2288O8.1, mediating cisplatin-resistance as well as affecting response of immunotherapy, could serve as a novel biomarker for forecasting prognosis and guiding clinical treatment in OC.